STRATEGIC APPROACHES TO FURTHER BUSINESS EDUCATION MANAGEMENT IN THE INTERNATIONAL COMPETITION CONTEXT - V. V. Gerasimenko; V. V. Molchanova (Управленческие науки)
Factors that contribute to more intense competition in the Russian business education market include the internationalization of business practices and the development of international management standards, which enhance the attractiveness of foreign business schools for the Russian consumers of educational services. The results of research carried out at the Faculty of Economics in Lomonosov Moscow State University illustrate the dynamic changes in the factors that determine the competitiveness in the Russian market for business education. The authors show that the new features of further professional business education providers’ strategic behavior appear in Russia: the emphasis is on network cooperation such as joint development of educational products with business organizations and foreign business schools, increased diversity of educational programs and new emphases in their content structure, with greater attention to international companies and networks management, cross-cultural communication in business, interdisciplinary aspects and global trends in the innovative development.